Pattern of stigma numbers as a taxonomic character in some didemnid ascidians (Aplousobranchia: Didemnidae) - Nagaya, Kazuhiko; Hirose, Euichi (Zootaxa, 2013)
Colonial animals are often lacking in taxonomic characters due to their small size and the simple morphology of zooids. Since zooid size is nearly uniform in many colonial ascidians, the stigma numbers in each row can be a useful taxonomic character. To evaluate their potential utility, we investigated intraspecific variations in stigma patterns in a subset of photosymbiotic didemnid ascidians, including five morphotypes of Didemnum molle, Lissoclinum midui, Trididemnum clinides, and T. nubilum. Stigma number patterns were almost stable in L. midui and T. nubilum. In contrast, there was considerable variation in stigma number even among clone zooids within the same colony in D. molle and T. clinides. Further, the stigma patterns did not differentiate the five morphotypes of D. molle. There was no significant correlation between the total number of stigma and the length of the thorax in any of the species examined here, suggesting that stigma number is probably invariable within each zooid. Stigma patterns can be usable as a taxonomic character in didemnid ascidians, particularly in species having one or a few patterns. Even in species with various patterns, the range of variation will be informative once such ranges are comprehensively described for didemnid species.